El trabajo de la memoria en Centroamérica: Cinco propuestas heurísticas en torno a las guerras en El Salvador, Guatemala y Nicaragua - Sprenkels, Ralph (2017)
This article presents a comparative exploration of contemporary memory work related to the wars of the second half of the twentieth century in three Central American countries: El Salvador, Guatemala and Nicaragua. It identifes fve different heuristic proposals forwarded to explain the essential features of these wars (including their main causes and consequences). I refer to these heuristic proposals respectively as “imposed oblivion,” “war among brothers,” “revolution,” “anti-communism,” and “disillusionment.” Linked to specifc political and historical sectors, these heuristic proposals have different levels of traction in each country. Their study allows to visualize the political arena of memory work in each country, while also providing input for an analysis of similarities and differences in war-related memory work between the three countries. Focusing on memory work as a contentious and relatively fragmented political process, the present article contributes to weighing the contemporary impact of war-related memory work in the Central American societies in question.